Insights and Challenges Business Incubation at Indonesian Universities - Widaharthana, I Putu Esa; Adyatma, Prastha (JUSTBEST Journal of Sustainable Business and Management, 2024)
Business incubators at universities have become a crucial component in fostering entrepreneurship and supporting startup development, especially in emerging economies like Indonesia. These incubators offer a supportive environment that helps entrepreneurs transform their ideas into successful businesses through mentorship, networking, and access to resources. However, despite their growing importance, business incubators in Indonesian universities face several challenges, including limited funding, regulatory hurdles, and a lack of experienced mentors. This literature review synthesizes existing research on university-based business incubators in Indonesia, exploring their role in the entrepreneurial ecosystem, the services they provide, and the obstacles they encounter. The review also highlights the contributions of these incubators to local economies and job creation, while addressing the gaps in research, such as the need for long-term impact assessments, sector-specific incubation models, and a deeper understanding of the regulatory environment. By identifying these challenges and opportunities, this review offers valuable insights for improving the effectiveness of university-based incubators in Indonesia, ultimately enhancing the country’s entrepreneurship landscape and contributing to sustainable economic growth.